EVALUASI PROGRAM PENANGANAN KEAMANAN DI SELAT MALAKA MELALUI OPERASI UDARA EYES IN THE SKY TNI AU - Waty, Sekti Ambar; Halimah, M.; S., Ramot C.P.; Suseto, Buddy; S., Ary Pitoyo (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2022)
The role of the Indonesian Air Force as an air force in the field of defense is to carry out air operations, one of which is implementing OMSP (Military Operations Other Than War). In carrying out operational activities, it is always based on state policies and political decisions. One of the efforts carried out by the Indonesian Air Force is to carry out security in the Malacca Strait; The Indonesian Air Force has joined with several countries in the area around the Malacca Strait in conducting the EIS (Eyes in The Sky) air operation, which has been ongoing since 2005. The formulation of the problem in this study is what are the obstacles in handling security in the Malacca Strait, what are the ideal condition in carrying out security handling in the Malacca Strait? And how efforts can be carried out in handling security in the Malacca Strait through EIS (Eyes In The Sky) Air Operations by the Indonesian Air. This study aims to obtain an overview of the form of evaluation needed by the Indonesian Air Force in implementing EIS Air Patrol activities following the theory that has been used as a reference. The research method used in this study is qualitative research. Primary data were obtained from informants from various agencies, and secondary data was obtained from credible sources such as books, reports, journals, and internet sources. The results of this study indicate that the presence of the EIS air patrol has not been effective in reducing the number of violations in the Malacca Strait; this is due to obstacles in the implementation of EIS air patrol activities as part of the Malaca Strait Patrol (MSP), including patterns of communication, cooperation, and coordination that have not materialized between implementing elements with one another. The next condition is that there is no similarity in the schedule of sea patrols held by the Maritime Sea Strait Patrol (MSSP) with air patrols held through EIS, so the mechanism for handling operations in the Malacca Strait, which is incorporated in the MSP (Malacca Strait Patrol) has not been realized.